Patient involvement in the implementation of infection prevention and control guidelines and associated interventions: a scoping review. Issue 3 (23rd March 2019) - Fernandes Agreli, Heloise; Murphy, Michael; Creedon, Sile; Ni Bhuachalla, Cliodhna; O'Brien, Deirdre; Gould, Dinah; Savage, Eileen; Barry, Fiona; Drennan, Jonathan; Smiddy, Maura P; Condell, Sarah; Horgan, Sinead; et al.
Abstract : Objective: To explore patient involvement in the implementation of infection prevention and control (IPC) guidelines and associated interventions. Design: Scoping review. Methods: A methodological framework was followed to identify recent publications on patient involvement in the implementation of IPC guidelines and interventions. Initially, relevant databases were searched to identify pertinent publications (published 2013–2018). Reflecting the scarcity of included studies from these databases, a bidirectional citation chasing approach was used as a second search step. The reference list and citations of all identified papers from databases were searched to generate a full list of relevant references. A grey literature search of Google Scholar was also conducted. Results: From an identified 2078 papers, 14 papers were included in this review. Our findings provide insights into the need for a fundamental change to IPC, from being solely the healthcare professionals (HCPs) responsibility to one that involves a collaborative relationship between HCPs and patients. This change should be underpinned by a clear understanding of patient roles, potential levels of patient involvement in IPC and strategies to overcome barriers to patient involvement focusing on the professional–patient relationship (eg, patient encouragement through multimodal educational strategies and efforts to disperse professional's power). Conclusions: There is limited evidence regarding the best strategies to promote patient involvement in the implementation of IPC interventions and guidelines. The findings of this review endorse the need for targeted strategies to overcome the lack of role clarity of patients in IPC and the power imbalances between patients and HCPs.